Low temperature plasma pretreatment enhances hot‐air drying kinetics of corn kernels. (25th July 2019) - Li, Shuai; Chen, Shanshan; Liang, Qing; Ma, Zhongsu; Han, Feng; Xu, Yan; Jin, Yi; Wu, Wenfu
Abstract: In this study, an efficient method for hot‐air drying of corn kernels was developed through a pretreatment of low temperature plasma. Corn kernels after plasma pretreatment were dried at 37.5, 45, and 52.5°C. It was found that the dried samples with plasma pretreatment presented shorter drying time and higher drying rate. After pretreatment power of 500 W for 30 s at 37.5°C, drying time was shortened by a maximum of 21.52%, and the drying rate was increased by 8.15%. The effective moisture diffusivity is in the range of 1.6107 – 1.9962, 2.8454 – 3.3600, 4.3237 – 4.7171 × 10 −11 m 2 s −1 at drying temperature of 37.5, 45, and 52.5°C. Plasma pretreatment enhances the drying kinetics more effectively with lower activation energy 47.79 kJ mol −1 in comparison with 54.82 kJ mol −1 for the control group. Atomic force microscopy showed the plasma pretreatment can change the surface topography with some microholes, which explain how the plasma pretreatment can improve the drying process. Practical Application: The low temperature plasma pretreatment can improve the efficiency of corn kernels drying. Furthermore, it has potential application for reducing energy consumption in drying. The low temperature plasma pretreatment can be potentially applied in commercial drying. Abstract :